The Effectiveness of Using YouTube as a Learning Media in Improving Early Childhood Literacy" - Andriyani, Maria; Maria Andriyani; Yenni Pudji Rahmawati (Schola, 2025)
This study aims to examine the effectiveness of using YouTube as a learning medium in improving early childhood literacy through the literature study method. Literacy is an important aspect of children's cognitive development that needs to be instilled early on. In the digital era, YouTube media is one of the interesting learning alternatives because it presents audio-visual content that can stimulate children's interest and understanding more optimally. This research was conducted by reviewing various scientific sources, journal articles, and relevant previous research results within the last five years. The results of the study show that the use of learning videos from YouTube, especially those containing letter recognition materials, vocabulary and children's stories, is proven to be able to improve literacy aspects such as the ability to recognise letters, understand initial sounds, and increase children's vocabulary. Educational animated videos presented with attractive colours, music and narration can create a fun and interactive learning atmosphere. Thus, it can be concluded that YouTube is an effective learning media in supporting early childhood literacy development, provided that its use must be directed and supervised by educators or parents wisely.